2000
DOI: 10.1021/ma000021d
|View full text |Cite
|
Sign up to set email alerts
|

Dendrimer−Polyelectrolyte Complexation:  A Model Guest−Host System

Abstract: Much experimental effort to realize possible uses of dendrimers has focused on the complexation of charged dendrimers to oppositely charged polyelectrolytes to form controlled delivery systems. Employing computer simulation and theory, we present a molecular-level picture of these guesthost aggregates and the conditions necessary for forming them. Specifically, we examine the equilibrium and dynamic complexation behavior of a monocentric dendrimer with charged terminal groups to a flexible, oppositely charged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
149
0
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(154 citation statements)
references
References 40 publications
3
149
0
2
Order By: Relevance
“…The linear-chain motion relative to the dendrimer in a complex has been studied by and was based on the snapshot MC simulation of Welch and Muthukumar [11], analysis. To characterize more quantitatively the motion of a chain relative to a dendrimer in a complex, the correlation functions ) ( 1 t P for unit vectors i c r directed from the dendrimer core to different PE monomers have been calculated, The rotation of a dendrimer as a whole occurs faster than the rotation m the dendrimer becomes slower when PE length increases.…”
Section: Chain Motion Relative To the Dendrimer Rotationmentioning
confidence: 99%
See 2 more Smart Citations
“…The linear-chain motion relative to the dendrimer in a complex has been studied by and was based on the snapshot MC simulation of Welch and Muthukumar [11], analysis. To characterize more quantitatively the motion of a chain relative to a dendrimer in a complex, the correlation functions ) ( 1 t P for unit vectors i c r directed from the dendrimer core to different PE monomers have been calculated, The rotation of a dendrimer as a whole occurs faster than the rotation m the dendrimer becomes slower when PE length increases.…”
Section: Chain Motion Relative To the Dendrimer Rotationmentioning
confidence: 99%
“…Theoretical consideration of such systems is restricted by their extreme complexity; in this case the use of computer-simulation methods becomes inevitable. First computer simulations of complexes formed by dendrimers with charged terminal groups and oppositely charged linear chains have been performed by Welch and Muthukumar [11] by Monte Carlo (MC). In their study only equilibrium characteristics, such as radius of gyration and a radial monomer density of the complex have been studied, although some suggestions about the mechanism of the relative-to-the-dendrimer linear-chain motion have been made [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of theoretical and computer simulation studies have been reported on structural properties of polyelectrolyte-dendrimer complexation under various conditions [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…4 To understand the selective interaction of bH1 with the LPS coated outer membrane of PA versus the eukaryotic cell membrane, we performed all atom molecular dynamics (MD) simulations of the dendrimer [5][6][7][8] interacting with membrane models constituted of a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC) bilayer as a model of the eukaryotic membrane, or of an asymmetric LPS on top of a 1,2-dipalmytoyl-3-phosphatydyl-ethanolamine (DPPE) layer as a model of the PA outer membrane (structure in ESI †). Standard MD protocols were followed using force field parameters and thermally equilibrated coordinates reported for POPC 9a and LPS.…”
mentioning
confidence: 99%